SP6 Acupressure Point for Reducing Joint Pain Among Elderly in Jombang Regency - Rajin, Mukhamad; Urifah, Siti; Hariyanto, Sufendi; Sa'diyah, Miranda Dwi (Al-Hijrah Indonesia, 2025)
Joint pain due to gout is common among the elderly and becomes a major issue if not treated. The resulting pain can interfere with daily activities and affect the quality of life of older adults. Long-term pharmacological treatment can lead to severe conditions; therefore, non-pharmacological interventions such as acupressure can be beneficial for elderly populations. This study aims to analyze the effect of SP6 (San Yin Jiao) acupressure therapy in reducing joint pain among the elderly. This was a pre-experimental study using a one-group pretest-posttest design. The sample consisted of 14 respondents selected through purposive sampling. SP6 acupressure therapy was administered twice a week for 5 minutes, involving 30 presses per session. Pain levels were measured using the Numerical Rating Scale (NRS). Data analysis using the Paired Sample T-Test showed a p-value of 0.000, which is less than 0.05, indicating that SP6 acupressure therapy significantly reduces joint pain in the elderly. This study supports the use of acupressure as a safe and affordable complementary therapy. Future research is recommended to extend the intervention duration and combine SP6 with other acupoints.